Self-Publishing and Collection Development Opportunities and Challenges for Libraries - Holley, Robert P. (Purdue University Press, 2015)
The current publishing environment has experienced a drastic change in the way content is created, delivered, and acquired, particularly for libraries. With the increasing importance of digital publishing, more than half the titles published in the United States are self-published. With this growth in self-published materials, librarians, publishers, and vendors have been forced to rethink channels of production, distribution, and access as it applies to the new content. Self-Publishing and Collection Development: Opportunities and Challenges for Libraries will address multiple aspects of how public and academic libraries can deal with the increase in self-published titles.
Description based on print version record.
KU Select 2016 Backlist Collection
Keywords: Language Arts & Disciplines / Library & Information Science / Collection Development; Language arts; Electronic books